Diseño de un modelo de comunicación y participación colectiva en seguridad y salud en el trabajo para la empresa Invesments & Business Global de la ciudad de Cartagena de Indias - Matute Berrio, Milton Manuel (Universidad Antonio Nariño, 2021)
The participation of workers in Safety and Health management implies their active incorporation in the planning, execution and evaluation of all activities for the prevention of occupational hazards. It is not possible to speak of participation when workers are only informed of the activities that are going to be carried out, or to speak of participation if a medical examination is carried out, a training course is given or when a survey is applied to them. without obtaining from them feedback and observations aimed at improving these and other activities that are part of the SG-SST